Effect of Iron Supplementation in Anti-Tuberculosis Drug Treatment on Interferon-Î³ Level in Tuberculosis Spondylitis Patients (Majalah Kedokteran Bandung, 2020)
Tuberculosis (TB) is still one of the major health problems in the community. Micronutrients, including iron, are crucial in the body's defense mechanism. Iron modulates the activation of IFN-Î³, which in turn will activate the macrophages. This study explores the effect of iron supplementation given with anti-tuberculosis drug therapy on the IFN-Î³ level in tuberculosis spondylitis patients. This was a single-blind randomized control trial study at Dr. Hasan Sadikin General Hospital Bandung, from December 2018 to March 2019, using the consecutive sampling approach. Thirty-four respondents with category 1 TB spondylitis and an sTfR level of> 21.7 pg /µL were recruited and randomized into control and experimental groups. The control group (n=17) was treated with 2 RHZE for 2 months while the experimental group (n=17) received 2 RHZE and iron tablet for 2 months. An increase in the IFN-Î³ level of the experimental group was observed from an average of 21.7 pg/ml before therapy to an average of 72.39 pg/mL after therapy. Meanwhile, the IFN-Î³ level in the control group increases from an average of 22.5 pg/mL to an average of 35.35 pg/mL. This difference was statistically significant based on the analysis using the independent t-test (p-value
Keywords: nterferon-Î³; iron supplementation; spondylitis TB